2020
DOI: 10.1534/g3.120.401635
|View full text |Cite
|
Sign up to set email alerts
|

Combining Auxin-Induced Degradation and RNAi Screening Identifies Novel Genes Involved in Lipid Bilayer Stress Sensing in Caenorhabditis elegans

Abstract: Alteration of the lipid composition of biological membranes interferes with their function and can cause tissue damage by triggering apoptosis. Upon lipid bilayer stress, the endoplasmic reticulum mounts a stress response similar to the unfolded protein response. However, only a few genes are known to regulate lipid bilayer stress. We performed a suppressor screen that combined the auxin-inducible degradation (AID) system with conventional RNAi in C. elegans to identify members of the lipid bilayer stress resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Mutant strains used are described at www.wormbase.org: LGI: eif-2a(qd338); LGII: cth-2(mg599), raga-1(ok386), spe-9(hc88), rrf-3(pk1426 and b26), eat-2(ad1116), rict-1(ft7) ; LGIII: rars-1(gc47), daf-2(e1368, e1370), glp-1(e2141), clk-1(qm30) ; LGX: atf-4(tm4397, tm4212) . Transgenic strains: LD1499 [P atf-4 (uORF)::GFP:: unc-54 (3’UTR)] was made by Chi Yun (1.8kb promoter 5’ of atf-4 including both uORFs into pPD95.75, personal communication with Chi Yun and David Ron) 63 .…”
Section: Methodsmentioning
confidence: 99%
“…Mutant strains used are described at www.wormbase.org: LGI: eif-2a(qd338); LGII: cth-2(mg599), raga-1(ok386), spe-9(hc88), rrf-3(pk1426 and b26), eat-2(ad1116), rict-1(ft7) ; LGIII: rars-1(gc47), daf-2(e1368, e1370), glp-1(e2141), clk-1(qm30) ; LGX: atf-4(tm4397, tm4212) . Transgenic strains: LD1499 [P atf-4 (uORF)::GFP:: unc-54 (3’UTR)] was made by Chi Yun (1.8kb promoter 5’ of atf-4 including both uORFs into pPD95.75, personal communication with Chi Yun and David Ron) 63 .…”
Section: Methodsmentioning
confidence: 99%
“…In C. elegans, the functional mapping and characterization of genetic pathways is typically done by identifying mutants with a desired phenotype (e.g., activation of a reporter gene, synthetic lethality with another gene, increased sensitivity to a chemical, etc.). These classical genetic approaches have been extremely useful in pathway mapping and have helped identify novel lipid metabolism regulators of the UPR-ER [13,14]. For example, recent efforts have used functional genomics approaches to identify new players in the UPR-ER LBS of C. elegans.…”
Section: Functional Genomic Approaches Identify New Upr-er Lbs Components In C Elegansmentioning
confidence: 99%
“…Specifically, a reverse genetic screen depleting 1247 predicted metabolic genes by RNAi yielded 34 genes whose inactivation induces the UPR-ER, including previously known players in lipid homeostasis and new candidates whose specific links to UPR-ER have not been explored [13]. Another study screened 712 kinase and transcription factor genes and identified 8 genes whose inactivation suppresses the UPR-ER LBS (induced by fat-6, mdt-15, or sams-1 RNAi) but not the UPR-ER PT (induced by heat or tunicamycin) [14]. This is exciting as it provides a list of new genes that may specifically activate the UPR-ER LBS or may selectively be required for a functional UPR-ER LBS , respectively.…”
Section: Functional Genomic Approaches Identify New Upr-er Lbs Components In C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of ATF-4 can be increased in response to endoplasmic reticulum (ER) stress through PERK1/PEK-1 phosphorylation of the initiation factor eIF2α, which reduces global translation rates [ 63 ]. PERK1/PEK-1 activation is also a hallmark of the ER unfolded protein response (UPR ER ) [ 64 ].…”
Section: Resultsmentioning
confidence: 99%